2021
DOI: 10.1101/2021.01.28.428465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High current production ofShewanella oneidensiswith electrospun carbon nanofiber anodes is directly linked to biofilm formation

Abstract: We study the current production of Shewanella oneidensis MR-1 with electrospun carbon fiber anode materials and analyze the effect of the anode morphology on the micro-, meso- and macroscale. The materials feature fiber diameters in the range between 108 nm and 623 nm, resulting in distinct macropore sizes and surface roughness factors. A maximum current density of (255 ± 71) μA cm-2 was obtained with 286 nm fiber diameter material. Additionally, micro- and mesoporosity were introduced by CO2 and steam activat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 49 publications
4
21
0
Order By: Relevance
“…A platinum mesh served as counter electrode. The bioelectrochemical reactor holds 1 L growth medium and six places for working electrodes (Erben et al, 2021b ). The anodes are mounted in holders that expose 2.25 cm 2 to the growth medium.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A platinum mesh served as counter electrode. The bioelectrochemical reactor holds 1 L growth medium and six places for working electrodes (Erben et al, 2021b ). The anodes are mounted in holders that expose 2.25 cm 2 to the growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…The current densities reported in the above publications are substantially lower than the current density achieved with an electrospun carbon nanofiber anode material (ES300), recently developed by our group, and are presumably limited by the anode materials. The superior current production of ES300 [(255 ± 71) μA cm −2 ] is directly linked to the biofilm growth on the anode (Erben et al, 2021b ). Analysis of the biofilm revealed that the biofilm fills only about 8 % of the material's pore space and that the available internal surface area is not completely covered with cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations